712 EVALUATING AN 'ACUTE FRAILTY TEAM' MODEL OF CARE IN IMPROVING OUTCOMES FOR PATIENTS WITH FRAILTY ACUTELY ADMITTED TO HOSPITAL. (8th March 2022) - Thompson, J; Gusev, V; Dervin, P; Tevendale, E
Abstract: Introduction: In frailty, Comprehensive geriatric assessment (CGA) has benefit in improving patient outcomes, including hospital readmissions and institutionalisation. We looked to evaluate the effectiveness of our newly initiated multi-disciplinary, acute frailty team (AFT) in improving acute care. This team works on the Acute Medical Unit (AMU), delivering early CGA alongside the existing acute medical care. Methods: The AFT initially targeted identification of frailty using the Rockwood clinical frailty score (CFS) through local quality improvement work. A standard operating procedure, encompassing CGA for all patients with frailty (define as a CFS 5 to 8 or, 4 with a frailty syndrome) was introduced. This assessment was additional to usual acute medical care. The impact was measured by retrospective case note review of 100 AMU admissions with frailty prior to the team being in post (Jan-March 2020) with a subsequent 100 patients seen by the AFT (March–April 2021). The 2 groups were matched for age, gender, frailty scores and pre-admission residence. These 2 cohorts were compared against key performance indices. Results: The mean age of patients in the Pre and post AFT cohorts were 85 years and 84 years respectively with an average CFS of 6. The identification and documentation of frailty improved in the AFT intervention cohort from 31% to 100% and screening for delirium with 4AT improved from 27% to 91%. The number of patients in the AFT cohort discharged directly from AMU increased from 5% to 14% with the average length of in-patient stay reducing from 10.2 days to 7.8 days. Thirty day remission fell from 23% to 16% in the AFT cohort, and the number of patients discharge to new 24 hour care declined from 21% to 9%. Conclusion: Our AFT alongside existing acute medical care improved outcomes including, frailty identification, delirium screening, length of stay, re-admissions and institutionalisation.